Punishment, politics and culture - Sarat, Austin; Ewick, Patricia (Amsterdam : Elsevier/JAI, 2004)
Beginning with an overview of the history and philosophy of punishment, these articles explore penal practices in the modern state and the deeper philosophical and social aspects of retributive justice.
Revisiting the history and philosophy of punishment. "Pattern penitence" : penitential narrative and moral reform discourse in nineteenth-century Britain / Anna Kaladiouk -- "Foremost among the prerogatives of sovereignty" : the power to punish and the death of comity in American criminal law / Karl B. Shoemaker -- Punishment, institutions, and justfications / Leo Zaibert -- Philosophical theories of punishment and the history of prison reform / Christopher Sturr. Penal practices in the modern state. Hitched to the post : prison labor, choice, and citizenship / Keally McBride -- Perhaps all pain is punishment : community corrections and the hyperghetto / William Lyons -- How science matters : discourse on deterrence in a death penalty debate / Theodore Sasson. Representing punishment in literature and popular culture. Executing sentences in Lolita and the law / Susan Elizabeth Sweeney -- The psychic life of punishment (Kant, Nietzsche, Freud) / Klaus Mladek -- Victim stories : documenting pain, punishment, prison and power / Alexandra Juhasz -- Remote justice : tuning in to small claims, race, and the reinvigoration of civic judgment / Valerie Karno.
Includes bibliographical references.
Description based on print version record.
Keywords: Punishment; Justice, Administration of -- Philosophy; Penology & punishment; Social Science -- Sociology -- General; Political Science -- Political Freedom & Security -- Law Enforcement